Production and microwave electromagnetic shielding effectiveness of polyaniline-La2Ti2O7:Er,Yb composites - GENÇ, SEVAL (KOREAN ASSOC CRYSTAL GROWTH, INC, 2021)
In this research, La2Ti2O7 doped with erbium-ytterbium was produced by using solid state technique. A series of compounds with the chemical equation (La1-x-yREx-y)(2)Ti2O7 were doped with (Er3+, x = 0.025, 0.050) and (Yb3+ y = 0.02) rare earth ions prepared by conventional solid state reaction method at 1350 degrees C for 24 h. X-ray diffraction (XRD), scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDS) were carried out for the structural analysis, which showed that second phase did not form in (La1-x-yREx-y)(2)Ti2O7. Additionally, the polyaniline- erbium, ytterbium doped La2Ti2O7 composites were fabricated via hot pressing using the compositions of (La0.955Yb0.02Er0.025)(2)Ti2O7, (La0.93Yb0.02Er0.05)(2)Ti2O7 and aniline. The weight ratios of erbium-ytterbium doped lanthanum titanate and aniline were 1:1 and 1:3 respectively, and epoxy resin was utilized to develop microwave shielding effectiveness composites. The microwave shielding effectiveness performances of polyaniline- La2Ti2O7: erbium-ytterbium composites were examined by shielding effect in 0-8 GHz using two-port vector network analyzer. A minimum of - 34.37 dB shielding effect performance was obtained in 6.27 GHz at the thickness of 2.0 mm. This shielding effect performance can be adjusted easily by managing the content of polyaniline in the composites for the needed frequency bands.
Keywords: Shielding effect; La2Ti2O7; Polyaniline; Polymer-matrix composite; ABSORBING PROPERTIES; OXIDE